The correlation of theoretical contact models for normal elastic-plastic impacts. (January 2020) - Wang, Hui; Yin, Xiaochun; Hao, Hong; Chen, Wensu; Yu, Bo
Abstract: In this study, eighteen elastic-plastic theoretical contact models are selected to investigate the spherical particle impacting on a half-space, where deformations occur on both objects. The analytical results of the selected theoretical contact models by using a spring-mass model are compared with the numerical results by using finite element analysis. The differences and correlations of the contact models are identified comprehensively by comparing the variations of the impact force, the indentation and the velocity of the particle during impact. Large discrepancies are found for the predictions of the loading and unloading impact behaviours by using different contact models. For different impact behaviours, including the maximum impact force, the maximum indentation, the impact duration, the permanent indentation and the coefficient of restitution, the analyses provide the corresponding matchable contact models both for indentation contact and flattening contact compared with finite element analysis results. Further analyses of the predicted impact behaviours by different contact models, especially analyses of the impact duration and the permanent indentation, reveal that the definition of the yield condition during loading phase as well as the effective radius of curvatures during unloading phase are important for contact models in predicting accurate local impact behaviours.